2010
DOI: 10.1093/ejechocard/jep232
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and haemodynamic significance of gas emboli during operative hysteroscopy: a prospective echocardiographic study

Abstract: Our study demonstrates a high frequency of continuous gas embolism during hysteroscopy, which is associated with a small but statistically significant increase in pulmonary artery systolic pressure without affecting right ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
2
20
0
2
Order By: Relevance
“…TEE-guided studies proved air bubbles during hysteroscopic surgery to occur in 98% of observed patients, without clinical repercussions [3]. Another paper found 85% of operative hysteroscopy patients to exhibit a continuous flow of bubbles through the right ventricle, again without clear clinical signs of an adverse event [2]. The incidence of symptomatic VAE at the author's institution during the studied time interval was surprisingly higher, likely due to a difference in surgical technique (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…TEE-guided studies proved air bubbles during hysteroscopic surgery to occur in 98% of observed patients, without clinical repercussions [3]. Another paper found 85% of operative hysteroscopy patients to exhibit a continuous flow of bubbles through the right ventricle, again without clear clinical signs of an adverse event [2]. The incidence of symptomatic VAE at the author's institution during the studied time interval was surprisingly higher, likely due to a difference in surgical technique (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Transesophageal echocardiography (TEE)-guided studies have shown that VAE occurs in the majority of operative hysteroscopies [2,3]. However, these studies have also suggested that these emboli are only rarely clinically significant.…”
Section: Introductionmentioning
confidence: 99%
“…Air bubbles were present in the right atrium (RA) of all patients; this finding was associated with transient desaturation, which resolved without intervention in 30% of cases. While not clinically significant, an increase in pulmonary artery pressure was observed in the majority of those patients [5].…”
Section: Introductionmentioning
confidence: 78%
“…Operative hysteroscopy carries a higher risk of gas embolism [3], with the incidence reaching 10% to 50% in one review [3]. A high incidence of asymptomatic gas embolization was found by Bloomstone et al in 2002, and recently confirmed by Leibowitz et al (2010) using transthoracic echocardiography (TTE) during operative hysteroscopy [4,5]. Air bubbles were present in the right atrium (RA) of all patients; this finding was associated with transient desaturation, which resolved without intervention in 30% of cases.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, the incidence of air embolism during surgery ranges from 7 to 69% as diagnosed by precordial Doppler [108]. Surgical procedures associated with pulmonary embolism include craniotomy [110], cervical spine surgery [111,112], cesarean section [113], laparoscopic cholecystectomy [114], hip arthroplasty [115] and hysteroscopy [116,117]. Additional risk procedures include central venous catheter insertion or removal [118,119], contrast administration [120], and the use of carbon dioxide for the visualization of the anastomosis during the off-pump coronary artery bypass grafting [121].…”
Section: Gas Pulmonary Embolismmentioning
confidence: 99%